Analis Pengembangan Modul Pembelajaran Berbasis Reciprocal Teaching Pair Share: Analyst Development of Learning Module Based on Reciprocal Teaching Pair Share - Widyaningrum, Diyah Ayu; Wahyuni, Lila (Universitas Muhammadiyah Sidoarjo, 2020)
This study aim determined the profile analysis of module needed based on Recripocal Teaching Pair Share learning model on Protist and Fungi material. The location used retrieved data was Taman Madya Malang High School. The method used in this study was the collection of qualitative descriptive data with an instrument in the form of a questionnaire to teachers and students. The resulted showed that teachers and students agreed with the development of Recripocal Teaching Pair Share (RTPS) based modules.